딸기 육묘장 토양 내 식물기생선충의 감염현황과 자묘를 통한 선충의 분산 - 고형래(Hyoung Rai Ko); 이민아(Min A Lee); 김은화(Eun Hwa Kim); 김세종(Se Jong Kim); 이재국(Jae Kook Lee) (Sigmulbyeong yeon'gu, 2017)
To survey the incidence of plant-parasitic nematode in strawberry nursery, 117 soil samples were collected from main producing area of strawberry nursery plants in 2016. The incidences of two major problematic nematodes such as root-lesion nematodes (Pratylenchus spp.) and root-knot nematodes (Meloidogyne spp.) were 11% and 3%, respectively. Strawberry nurseries using upland soil either in fields or in plastic-houses showed were higher infection rates of Pratylenchus spp. or Meloidogyne spp. than others. On the other hand, a strawberry nursery using pots filled with bed soil in plastic-house was the lowest infection rate with 0%. Phylogenetic relationships and distance analysis were performed for identification of Pratylenchus spp. and Meloidogyne spp. detected from strawberry nurseries. As the results, they were identified as Pratylenchus penetrans, Pratylenchus vulnus and Meloidogyne hapla. Meanwhile, when nursery plants of strawberry infested with P. vulnus transplanted to pots filled with sterilized soil, P. vulnus was detected from soil in pots as 33% frequency. Thus, P. vulnus can be spread through nursery plants of strawberry infested with that. These studies suggested that Pratylenchus spp. and Meloidogyne spp. were ploblematic nematodes in major areas of strawberry nursery plants and P. vulnus could be spread through nursery plants of strawberry. 2016년 6월부터 9월까지 국내 딸기 육묘장 117개 포장의 토양으로부터 식물기생선충의 토양 내 감염현황을 조사하였다. 그 결과 뿌리썩이선충(Pratylenchus)과 뿌리혹선충(Meloidogyne)이 11%와 3%로 검출되어 딸기 육묘장의 문제선충으로 나타났다. 육묘 형태별로는 토경육묘에서 뿌리썩이선충과 뿌리혹선충의 발생빈도가 다른 육묘방법에 비해 높았고, 상토를 이용한 비가림 포트육묘에서는 식물기생선충이 검출되지 않았다. 뿌리썩이선충은 딸기뿌리썩이선충(P. penetrans)과 사과뿌리썩이선충(P. vulnus) 2종이 확인 되었으며, 뿌리혹선충은 당근뿌리혹선충(M. hapla) 1종이 확인되었다. 사과뿌리썩이선충은 딸기 자묘를 통해 식물기생선충이 감염되지 않은 건전한 토양으로의 확산이 확인되었다(33%).